2018
DOI: 10.17219/acem/79846
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of selected genes in tumors and matched surgical margins in oral cavity cancer: Do we have to pay attention to the molecular analysis of the surgical margins?

Abstract: Background. Head and neck squamous cell carcinomas (HNSCCs) are associated with an interplay between genetics and the environment; they account for 3% of all diagnosed malignant tumors in men and 2% of those in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In recent years, there have also been tested a number of studies investigating the role of various genetic and molecular factors in postoperative material and surgical margins -including PTEN [56], TIMP3, SFRP1, SFRP2, CDH1, RASSF1, RORA, DAPK1 [57], TIL -tumour-infiltrating lymphocytes [58] and many others [59][60][61]. However, a clear statement of their clinical utility requires further research.…”
Section: Histologymentioning
confidence: 99%
“…In recent years, there have also been tested a number of studies investigating the role of various genetic and molecular factors in postoperative material and surgical margins -including PTEN [56], TIMP3, SFRP1, SFRP2, CDH1, RASSF1, RORA, DAPK1 [57], TIL -tumour-infiltrating lymphocytes [58] and many others [59][60][61]. However, a clear statement of their clinical utility requires further research.…”
Section: Histologymentioning
confidence: 99%
“…Several studies have investigated the potential of epigenetic changes in normal adjacent margins of the tumor as prognostic factors for OSCC patients [ 24 , 25 , 26 , 27 ]. Most of them showed that NAT samples, even if histologically negative for cancer cells, already have changes that can affect diagnosis and prognosis [ 27 , 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%